OPTIMAL LEVEL OF FOREIGN RESERVES – EXAMPLE OF BOSNIA AND HERZEGOVINA - Tijana Šoja (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2014)
The paper points to the conceptual definition of foreign exchange reserves, the role, importance and objectives for holding foreign exchange reserves as well as evaluating the required amount of foreign exchange reserves, or adequacy of foreign exchange reserves. Foreign exchange reserves are important assets in each country and they are significantly affected by monetary policy, exchange rate policy or regulation and external instability and the impact of the crisis that may come from the environment. This paper presents a simple way of estimates of adequacy and optimality of foreign exchange reserves, which are basis for the analysis of foreign exchange reserves, as well as in the construction of statistical and mathematical models that detail the optimal level of international reserves. Special review was paid to the assessment of the adequacy of foreign exchange reserves of Bosnia and Herzegovina, and the Central Bank of Bosnia and Herzegovina.